Diseases associated with ocular surface abnormalities: the importance of reflex tearing. Issue 1 (1st January 1999) - Tsubota, Kazuo; Kaido, Minako; Yagi, Yukiko; Fujihara, Tsutomu; Shimmura, Shigeto
Abstract : AIM: To investigate the correlation between tear function tests and ocular surface integrity in patients with dry eye. METHODS: 297 dry eye patients (55 Sjögren's syndrome, two male and 53 female, average age 52.4 (SD 15.0) years, and 242 non-Sjögren's syndrome, 41 male and 201 female, average age 53.5 (14.1) years) were examined. The following tear function tests were performed: (1) cotton thread test, (2) Schirmer test with topical anaesthesia, (3) Schirmer test without anaesthesia, (4) Schirmer test with nasal stimulation, (5) tear clearance test, and (6) tear break up time (BUT). The ocular surface was evaluated by rose bengal and fluorescein staining. Correlation analysis was performed between each tear function index and vital staining scores. RESULTS: Among the six tear function tests, the Schirmer test with nasal stimulation correlated most with both of the vital stains (ρ=0.530 for rose bengal and 0.393 for fluorescein). The Schirmer test with or without anaesthesia correlated slightly with rose bengal staining, whereas tear clearance test and tear break up time slightly correlated with fluorescein staining. CONCLUSION: Vital staining of the ocular surface correlates most with reflex tearing measured by the Schirmer test with nasal stimulation.